Analisis Dan Perancangan Sistem Informasi Manajemen Arsip Pada Dinas Tanaman Pangan Hortikultura Dan Peternakan UPTD-BPSPT Provinsi Jambi - Nurrahayu, Ulfah; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2021)
The archive management information system at the UPTD-BPSPT Jambi Province Food Crops, Horticulture and Livestock Service is currently still being done manually. Where archiving still records using an agenda book in recording existing archive activities. As well as data / files that will be archived have a different encoding or archive number. This results in frequent reports that data that is not ren will be processed. Because of this, delays often occur in the preparation of reports, and the related employees must re-verify the data / files in the relevant sections. Existing data / files are also stored manually. Where they still use the help of filing cabinets for storage. This archive management information system is designed for the process of archiving data / files at the UPTD-BPSPT Jambi Province Food Crops, Horticulture and Livestock Service. This system is designed using the Unified Modeling Language (UML) object-based modeling technique in the form of use case diagrams, activity diagrams, and class diagrams. The output of this research is a prototype design of the archive management information system at the UPTD-BPSPT Food Crops, Horticulture and Animal Husbandry Department of Jambi Province.